Development of a Guided Inquiry-Based Biology Practicum Guidebook Integrating Scientific Literacy in Support of SDG 4: Quality Education - Ericka Darmawan; Weni Anggraini; Setya Agustina (Journal of Current Studies in SDGs, 2027)
Objective: To develop and evaluate the feasibility and practicality of a guided inquiry-based biology practicum guidebook integrating scientific literacy for Grade XI high school students. The guidebook was designed to support structured laboratory learning and contribute, at the instructional-resource level, to Sustainable Development Goal 4 by providing a quality learning resource for biology education.  Method: Employed a research and development approach using the 4-D model modified into three stages: define, design, and develop. Data were collected through interviews, needs-analysis questionnaires, expert validation, and limited-scale trials. The developed product was assessed by material and media experts and evaluated using response questionnaires completed by two biology teachers and participating students. The quantitative data were analyzed using descriptive percentage analysis. Results: The material expert validation produced an average score of 98.66%, while the media expert validation reached 98%, with both categorized as very good. Teacher responses yielded an average practicality score of 93.52%, whereas student responses reached 84.53%, also within the very good category. These findings demonstrate that the guidebook is highly feasible and practical as a supporting resource for biology practicum activities. Novelty: To integrate guided inquiry stages, laboratory procedures, safety guidance, reporting formats, and scientific literacy tasks within a single practicum guidebook aligned with Phase F biology learning. This integrated design offers a contextual instructional resource that facilitates active investigation, evidence-based reasoning, and quality science education consistent with SDG 4.